Dampak Penyelenggaraan Festival Seni Budaya Terhadap Aspek Ekonomi Masyarakat di Desa Adat Kuta - Putra Diatmika, Sang Bagus Putu Wira; Citrawati, Luh Putu; Sumadi, I Gede (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan DigitalDO - 10.30647/jpbd.v2i2.2112, 2026)
This study aims to examine the economic impact of the Cultural Arts Festival on the local community in Kuta Traditional Village, Badung Regency. Cultural arts festivals are regarded as a form of tourism event with significant potential to stimulate local economic growth through increased income, job creation, and community economic circulation. This research employs a quantitative approach, using data collection techniques such as observation, interviews, and questionnaires distributed to 100 respondents. The findings indicate that the festival has a positive impact, evidenced by increased economic transactions, participation of MSMEs, the creation of seasonal jobs, higher community income, and enhanced destination image promotion. However, there are also negative impacts, including traffic congestion, rising prices of basic necessities during the festival, and increased waste production. Overall, the average respondent rating on the economic impact falls under the "agree" category, with a mean score of 4.23 (very good). Based on these results, it is recommended to enhance the festival’s sustainability by improving traffic management, implementing more effective waste management, and maintaining price stability throughout the event. Keywords: cultural arts festival economic impact, tourism event